2018
DOI: 10.1186/s12884-018-2038-0
|View full text |Cite
|
Sign up to set email alerts
|

Postpartum quality of life in Indian women after vaginal birth and cesarean section: a pilot study using the EQ-5D-5L descriptive system

Abstract: BackgroundThere has been little evaluation of the postpartum quality of life (QOL) of women in India and its association with the mode of birth. This study piloted the use of the generic EQ-5D-5L questionnaire to assess postpartum QOL experienced by rural Indian women.MethodsA convenience sample of rural women who gave birth in a health facility in Gujarat or Madhya Pradesh was recruited into this pilot study. QOL was measured during three interviews within 30 days of birth using the EQ-5D-5L questionnaire. Pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
39
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(49 citation statements)
references
References 27 publications
3
39
0
2
Order By: Relevance
“…In contrast, the findings of a cohort study performed on primiparous women of a large Danish population showed that hyperemesis-gravidarum, hypertension, pre-eclampsia, and caesarean section were associated with increased risk of PPD [7]. Similarly, a study on women in rural Indian revealed that vaginal delivery (even with an episiotomy) was associated with higher postpartum quality of life (QoL) than caesarean delivery [45]. Differences between the results of the current study and other studies may be due to the number of samples, area of study, study design and tools of data collection.…”
Section: Discussionmentioning
confidence: 97%
“…In contrast, the findings of a cohort study performed on primiparous women of a large Danish population showed that hyperemesis-gravidarum, hypertension, pre-eclampsia, and caesarean section were associated with increased risk of PPD [7]. Similarly, a study on women in rural Indian revealed that vaginal delivery (even with an episiotomy) was associated with higher postpartum quality of life (QoL) than caesarean delivery [45]. Differences between the results of the current study and other studies may be due to the number of samples, area of study, study design and tools of data collection.…”
Section: Discussionmentioning
confidence: 97%
“…This review laid out the relevance of the facilities' ownership in materno-fetal and neonate CSDrelated outcomes. Of the 14 studies targeting both public and private facilities [4,45,48,[52][53][54][55]57,[59][60][61][62]64,65], only Murta et al [60] and Kilsztajn et al [59] have frontally compared the CSD outcomes between participants in public and private institutions. In the case of the former, private institutions led statistically to fewer LBW babies (OR = 1.4 vs. 2.33), while in Kilsztajn et al's study, the likelihood of dying from CSD was 3.3 times higher [59].…”
Section: Discussionmentioning
confidence: 99%
“…and Quality Adjusted Life Days (QALDs). Thus, Kohler et al [52] found that the VD group had a higher QOL (0-3 days postpartum: 0.28 vs. 0.57, 3-7 days postpartum: 0.59 vs. 0.81; p < 0.001) and was more likely to report no or slight problems in 4 of 5 health dimensions (mobility, self-care, usual activities, pain or discomfort; p < 0.04) during interviews (1 st and 7 th days). Similarly, in Nepal, Sharma and Dhakal [49] found that VD led to fewer complications for mothers compared to CSD (39%, vs. 53.5%) and likewise for newborns (28.4% vs. 52.1%).…”
Section: Several Authors Have Approached the Comparison Between Csd Omentioning
confidence: 99%
See 1 more Smart Citation
“…At Muhimbili National Hospital (MNH), 52.5% of patients undergoing labour induction receive Complication free vaginal delivery is the primary goal of labour induction 7,8 . A method that is associated with increased vaginal birth would enhance women's Health Related Quality of Life (HRQoL) post-delivery 23 . Postpartum women following vaginal birth are less likely to have problems with mobility, self-care, routine activities, pain or discomfort 23 .…”
Section: Introductionmentioning
confidence: 99%